A study titled The Role of Management in Building Corporate Culture and Improving Organizational Performance-An Applied Study in Building Research Department (Czech Journal of Multidisciplinary Innovations, 2025)
The research aims to identify the role of management in building the culture of the security institution and organizational performance. The problem was represented by the extent of the impact of general culture on enhancing organizational performance for the organizational research department, which affects individuals through culture, values, and festivals, and thus their repercussions on organizational performance . The study used the descriptive analytical approach, and to achieve this, a questionnaire form was designed for employees working in the Building Research Department, and they were randomly selected as a study sample that includes (40) employees. Data were collected, analyzed, and hypotheses were tested using statistical methods (SPSS) for the social sciences. The study came out with a number of results: If the results of the statistical analysis showed the existence of a statistically significant effect between the dimensions of organizational culture: (shared vision, culture of teamwork) and the organizational performance of the Construction Research Department. Shared vision affects organizational performance by (0.415). In other words, the more employees in the Construction Research Department are aware of the concept of shared vision, the more organizational performance improves by (0.415). The study emphasized the importance of having a distinct organizational culture within the department, one that works at all administrative levels to consolidate and instill its principles, reflecting the company's values and directions among its employees .